The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41467-018-04926-x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal tolerance is a subpopulation effect distinct from resistance and is associated with persistent candidemia

Abstract: Tolerance to antifungal drug concentrations above the minimal inhibitory concentration (MIC) is rarely quantified, and current clinical recommendations suggest it should be ignored. Here, we quantify antifungal tolerance in Candida albicans isolates as the fraction of growth above the MIC, and find that it is distinct from susceptibility/resistance. Instead, tolerance is due to the slow growth of subpopulations of cells that overcome drug stress more efficiently than the rest of the population, and correlates … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
319
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(362 citation statements)
references
References 81 publications
14
319
3
Order By: Relevance
“…Microbial cultures show molecular and phenotypical heterogeneity that may be important within the scope of antimicrobial resistance (33). Histogram graphs of the calcofluor staining showed that the increase in chitin content is at a sub-population level (Fig 7B).…”
Section: Resultsmentioning
confidence: 99%
“…Microbial cultures show molecular and phenotypical heterogeneity that may be important within the scope of antimicrobial resistance (33). Histogram graphs of the calcofluor staining showed that the increase in chitin content is at a sub-population level (Fig 7B).…”
Section: Resultsmentioning
confidence: 99%
“…That is, the source of the cells physiological ability to survive in the presence of the inhibitory compound is not due to stable genomic modifications, but rests upon post-transcriptional programs such as position in the cell cycle, expression of stress genes, or random fluctuation in key cellular defense genes. In general, tolerance is not nearly as well understood as drug resistance 37,38 . Even when grown under standard laboratory conditions, isogenetic (or near isogenic) Candida populations respond differentially to antifungal drugs, with some fraction of the population exhibiting drug tolerance, defined as the ability of individuals to survive and grow at drug concentrations above the minimal inhibitory concentration (MIC) 37,39 .…”
Section: Introductionmentioning
confidence: 99%
“…Antifungal drug tolerance, a property distinct from drug resistance (2,3) , is the ability of some cells in a strain to grow slowly in the presence of a drug at concentrations above the MIC. In tolerant strains, the subpopulation of cells that grow (generally from 10-90% of cells, depending on the strain) is usually evident when growth is assessed after 48 h or longer in the drug (reviewed in 4) .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the failure to clear infections is more likely when the infecting strain is drug-resistant. High levels of drug tolerance also may influence infection clearance (3,7) , although more studies that use quantitative criteria to definitively measure tolerance levels and distinguish tolerance from resistant isolates are needed (reviewed in 4) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation